The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s00345-011-0713-0
|View full text |Cite
|
Sign up to set email alerts
|

Computerized transrectal ultrasound of the prostate in a multicenter setup (C-TRUS-MS): detection of cancer after multiple negative systematic random and in primary biopsies

Abstract: The results indicate that C-TRUS-MS "online" achieves similar results as the stand-alone system, independent of the user even with little experience in the method. Furthermore, C-TRUS-MS for the first time is able to detect carcinomas in patients without prior biopsies in a high number by taking only six targeted biopsies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 24 publications
0
14
2
2
Order By: Relevance
“…Furthermore, PCa detection rates with 39-139 systematic cores have been reported at 45%, which is a lower detection rate than our results using a median of 5 E-TRUS targeted cores [14]. Recently, Grabski et al [15] reported in a prospective multicenter study PCa detection rates even in patients without prior biopsies, up to 41% by taking only six targeted cores when using a computerbased analysis of the TRUS signal. Furthermore, even we know that our technique needs expensive equipment, saturation biopsy has significantly higher costs of at least 5,000 USD compared with standard systematic biopsy.…”
Section: Discussioncontrasting
confidence: 74%
“…Furthermore, PCa detection rates with 39-139 systematic cores have been reported at 45%, which is a lower detection rate than our results using a median of 5 E-TRUS targeted cores [14]. Recently, Grabski et al [15] reported in a prospective multicenter study PCa detection rates even in patients without prior biopsies, up to 41% by taking only six targeted cores when using a computerbased analysis of the TRUS signal. Furthermore, even we know that our technique needs expensive equipment, saturation biopsy has significantly higher costs of at least 5,000 USD compared with standard systematic biopsy.…”
Section: Discussioncontrasting
confidence: 74%
“…Our detection rate (20%) is lower than the rates reported in the literature [23] [24] [25] [26]. This difference is explained by our "blind" method which limits the detection of small non-palpable fireplaces DRE.…”
Section: Cancer Detection Ratecontrasting
confidence: 73%
“…There are only a few studies regarding the ANNA/C-TRUS technology. To date, it was able to be shown that prostate cancer was able to be detected in 31 of 75 patients (41 %) via targeted 6-core biopsy of areas suspicious on ANNA-C-TRUS [19]. These results were able to be confirmed in another study with 20 patients.…”
Section: Computer-assisted Ultrasoundmentioning
confidence: 62%